(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2024)
The article deals with the issue of students’ communicative competence formation through teaching literary discourse at foreign languages departments of pedagogical university. Special attention is paid to the discourse competence as a constituent of the communicative competence. The aim of the work is to consider literary discourse as a unit of communication and suggest a methodological model for discourse competence formation on the base of specific tasks. The results of the research can be formulated as follows. Literary discourse, as an act of communication between the creator of the text and the reader, is a communicative unit around which the educational process is organized. The article emphasizes that students’ discourse competence depends on the students’ ability to interpret literary discourse. For successful interpretation of literary discourse students acquire certain discursive skills. The article specifies discursive skills taking into account mental-communicative nature of literary discourse and suggests relevant conditions for development of these skills. Discursive skills are developed gradually through the tasks affecting the activation of learners’ thinking processes: from the level of knowledge to the level of evaluation (according to B. Bloom’s taxonomy). The communicative interaction ``author – addressee’’ is shifted form one situation to another due to the tasks to perform cognitive actions of different levels. Level 1 – perception of the author’s intention is through the tasks for structural and syntactic analysis of the text, analysis of the lexical level of the text, means of contact with the reader, prediction of the author’s intentions. Level 2 – understanding of the author’s intentions is through the author’s (characters’, reader’s) questions and their answers. Level 3 – application of the information is through using it in new situations related to the reader’s experience. Level 4 – analysis of the information is through analysis of the causes of the characters’ actions and their consequences, assessment of what is happening by the author and the reader. Level 5 – Synthesis of the information is through the creation of new texts on behalf of the author or a character in various text forms. Level 6 – evaluation of the literary discourse. It is based on designed assessment criteria which are classified into 6 groups: the formal side of the discourse, content, characters, effect of the literary discourse, language means, and author-reader interaction. The important role of elective courses aimed at interpreting literary discourse for high schools as well as for senior profile schools is stressed.